Características de suelo y usos tradicionales de especies vegetales en la Provincia de Huaraz, Ancash, Perú - Olivera Gonzales y Cols., Percy (2019)
This study give knowlege about 20 species of plants from Huaraz Province: Acacia macracantha., Alnus acuminata, Ambrosia arborescens, Baccharis latifolia, Barnadesia dombeyana, Caesalpinia spinosa, Cordia lutea., Furcraea andina, Jungia paniculata, Mutisia acuminata, Oreocalis grandiflora, Ophryosporus angustifolius, Polylepis incana, Schinus molle, Senecio elatus, Tecoma sambucifolia., Sambucus peruviana, Verbesina sp, y Baccharis sp.; and one introduced specie Spartium junceum. It was determinated the textural soil by the hidromether method, the pH by the electromether method and the use tradicional of each one. It was found that each one species grow in soils with diferent texture, where the more frecuently were sandy loam and loamy sand, and in the same way the pH can be different.